Military strategy a global history - Black, Jeremy 1955 (Yale University Press, 2020)
Strategy has existed as long as there has been organised conflict. In this new account, Jeremy Black explores the ever-changing relationship between purpose, force, implementation and effectiveness in military strategy and its dramatic impact on the development of the global power system. Taking a 'total' view of strategy, Black looks at leading powers - notably the United States, China, Britain and Russia - in the wider context of their competition and their domestic and international strengths. Ranging from France's Ancien Regime and Britain's empire building to present day conflicts in the Middle East, Black devotes particular attention to the strategic practice and decisions of the Kangxi Emperor, Clausewitz, Napoleon and Hitler